How Foreign Participation and Market Concentration Impact Bank Spreads: Evidence from Latin America - Martinez Peria, Maria Soledad; Mody, Ashoka (World Bank, Washington, D.C., 2013)
Increasing foreign participation and high concentration levels characterize the recent evolution of banking sectors' market structures in developing countries. The authors analyze the impact of these factors on Latin American bank spreads during the late 1990s. Their results suggest that foreign banks were able to charge lower spreads relative to domestic banks. This was more so for de novo foreign banks than for those that entered through acquisitions. The overall level of foreign bank participation seemed to influence spreads indirectly, primarily through its effect on administrative costs. Bank concentration was positively and directly related to both higher spreads and costs.